KARAKTERISTIK FISIK HABITAT TARSIUS (Tarsius dentatus) DI KAWASAN TAMAN NASIONAL LORE LINDU - Krisnatalia, Ella; Wardah, Wardah; Ihsan, Moh. (Warta Rimba, 2013)
Sulawesi Island is a transition island from Asia and Australia continent. Sulawesi especially Lore Lindu National Park is a habitat of endemic and scarce animal such as tarsier (Tarsius dentatus). The population of tarsier is decreasing caused by its habitat has damaged from time to time. Therefore, it needs to conduct a research to know the physical characteristic of tarsier habitat. Some Information about the slope, temperature, light intensity might help the management of tarsius endemic animal. This research applied descriptive method that was conducted within field orientation to get information about the habitat of tarsier. Also, the data was gotten by asking the society around habitat of Tarsius dentatus. Based on the result of the research, the habitat or tarsier has 694m asl of height,with 10% slope. The air temperature around 20Â°C-28Â°C, with the air dampness around 70%-84,3%. Iluminitas level acepted from 2000lux up to 83000 lux. Keywords : Tarsier (Tarsius dentatus), Habitat, Lore Lindu National Park.